Charging and discharging methods for modularized battery energy storage systems (MBESS) - Kandasamy Karthik (2016)
Electric vehicles (EV) promise to be a panacea to address the pressing problem of global warming from greenhouse gas emissions. EV possesses the potential to radically transform the personal transportation sector in the near future. The research studies related to EV are multi-disciplinary, comprising of material science, electro-chemistry, power electronics, mechanical, embedded systems etc. This research primarily focuses on the study of operation and control of power converters that are suitable for EV application. Modularization and swapping of battery system are taken as major approaches in this research study to improve the reliability of EVs from the energy source standpoint. Conventionally, the battery pack and hence the power converters employed for charging and driving the motor in an EV are monolithically constructed. Consequently, the operation of EV completely depends on a single energy source. Alternatively, modularizing the energy source could greatly increase the operational reliability of an EV and thus the necessity of modularizing the power converters arises. The charging time required by the EVs is significantly longer when compared with the time required to refuel a gasoline vehicle. This is considered as the debilitating disadvantage for the electric vehicle commercialization. Hence, instead of charging the battery in the EV, swapping the depleted battery with another charged battery could ameliorate the afore-mentioned disadvantage. The novel inductive power transfer (IPT) concept is considered for implementation to improve the performance of this battery swapping process. Two systems incorporating IPT are proposed and analysed as a part of this research study. The Cascaded H-bridge (CHB) multi-level converter is generally considered an apt choice when multiple DC sources are available as in the case of modularized battery energy storage system (MBESS). This work investigates a battery module/micro-pack level SOC balancing control in a CHB based MBESS using Multi-dimensional pulse width modulation (MD-PWM). MD-PWM is a generalized modulation strategy for CHB converters, and a review of which is conducted. Modular battery pack system or micro-pack concept for CHB is introduced to increase the availability of the EV in the event of fault. A control strategy is proposed for the SOC balancing between the battery micro-packs in the CHB. This proposed control strategy aims to deliver a semblance of uniform operation of the whole battery system irrespective of the current SOC of each micro-pack. The realization of fault tolerant operation using MD-PWM is also proposed. The advantage of the proposed methods is that it can be conveniently integrated with the MD-PWM algorithm, eliminating any external circuit. The results obtained from the laboratory setup of a five-level three-phase CHB with six battery modules of 15 V 6.2 Ah is presented for RL load. The results obtained from the laboratory setup of a five-level three-phase CHB driving an induction motor with six battery modules of 52.8 V 60 Ah is also presented. The results verify that the fault tolerant and SOC balancing operation can be achieved with CHB using MD-PWM. The results demonstrates the need of SOC balancing, and efficacy of the proposed methods in achieving fault tolerant as well as SOC balanced operation to prolong the system operation. A modularized battery system with Double Star Chopper Cell (DSCC) based modular multilevel converter is proposed for a battery operated electric vehicle (BEV). A conceptual design of lithium ion based battery micro-packs for DSCC is described. MD-PWM with integrated inter-module SOC balancing and fault tolerant control for DSCC is proposed and explained. The methods of operation of the DSCC as an inverter and as a synchronous rectifier using MD-PWM with integrated inter-module SOC balancing and fault tolerant control is discussed. The performances of the DSCC for SOC balancing and fault tolerant operations are verified through simulations of a 28 kWh BESS with DSCC and the results are discussed. Another objective of reducing the down-time of an EV is achieved by implementing battery swapping regime. To realize a replaceable and modularized energy storage system with wireless interface, two topologies are proposed for a battery operated EV. The proposed systems are analysed from the power converters operation and the Inductive Power Transfer (IPT) perspective. The proposed systems would have a casing (hollow compartment fitted to the vehicle chassis) that can accommodate certain number of modules (box like structure). The casing side is deployed with IPT secondary side which is connected to the DC link of the inverter driving the motor. The module (box like structure) side is deployed with the battery micro-pack and IPT primary side. First topology is comprised of multiple and independent module-casing combination, whereas the second topology is comprised of multiple modules inside a single casing. The operation of the first topology is analysed with an equivalent circuit and an averaged state-space model. A feedback linearization technique to establish the DC link voltage regulation based on the phase shift ratio between the primary side and the secondary side voltages is implemented. The power flow is controlled using the module side converter to maintain the DC link voltage at the three-phase inverter driving the three-phase load. The second topology is analysed with an equivalent electric circuit and the expressions for power flow are derived using steady state analysis of the equivalent circuit. The operation and control of the proposed systems are described, presenting steady state analysis and simulation results of an 80 kW system. Laboratory prototypes of 1.5 kW systems for each topology with IPT interfaces are built, and the results from both simulations and the laboratory prototypes are presented and discussed. The results show that the power flow from the battery modules can be controlled independently. Thus the operational reliability and the availability of an EV could be potentially enhanced by employing the proposed system which offers modularity and would make the battery swapping process more safe, convenient and reliable.